Pelestarian dan Pemeliharaan Koleksi Bahan Pustaka di SMA Negeri 3 Tualang Kabupaten Siak Provinsi Riau - Fijas, Felya Invita; Marlini, Marlini (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2020)
ABSTRACT SMA Negeri 3 Tualang, Kab. Siak is one of the schools in Siak Regency, Riau. This search describe preservation and maintance activities which are carried out as an effort to save information in the library material collection of SMA Negeri 3 Tualang, Kab. Siak library. To find out of the activities carried out by the library of SMA Negeri Tualang, Kab. Siak, the author conducted research through qualitative methods. In finding this information, an interview was conducted with one of the librarians of SMA Negeri 3 Tualang, Kab. Siak to get information about the activities of preserving and maintaining the library collections at SMA Negeri 3 Tualang, Kab. Siak, Riau. The results of this study explain that the factors of damage to library materials in the library of SMA Negeri 3 Tualang, Kab. Siak, Riau are such as bookworms, mice, dust and humans. Efforts made to prevent damge such as cleaning dust regularly, providing camphor around the library and collection shelves, and providing warning and sanctions for damage caused by students and attempts to repair damage by photocopying damage collections pages and restocking. Keyword: preservation, library, collections.